Optical and thermal properties of TeO2-B2O3-Gd2O3 glass systems - Muhammad Noorazlan Abd Azis (Tanjong Malim, 2019)
Optical and thermal properties of TeO2-B2O3-Gd2O3 glass systems by Muhammad Noorazlan Abd Azis